Do Bioflavonoids in Juniperus virginiana Heartwood Stimulate Oviposition in the Ladybird Coleomegilla maculata?. (27th February 2018) - Riddick, Eric W; Wu, Zhixin; Eller, Fred J; Berhow, Mark A
Maximizing the reproductive potential of ladybird beetles fed factitious foods or artificial diets, in lieu of natural prey, is a major challenge to cost-effective mass rearing for augmentative biological control. In this study, we tested the hypothesis that compounds in redcedar, Juniperus virginiana, stimulate oviposition in the ladybird Coleomegilla maculata . We also tested the prediction that several bioflavonoids, identified in heartwood fractions, elicited this behavioral response. Phenolic compounds were extracted from J. virginiana heartwood sawdust, separated into several fractions, then presented to adult beetles, in a powdered, pure form, in the laboratory. Females preferentially oviposited within 1 to 2 cm of fractions B, C, D, and E, but not A or the unfractionated extract, at the base of test cages. Chemical analysis identified bioflavonoids in heartwood fractions and subsequent bioassays using several identified in fractions C, D, and E confirmed that quercetin, taxifolin, and naringenin (to a lesser extent) stimulated oviposition. All tested fractions and bioflavonoids readily adhered to the chorion of freshly laid eggs but did not reduce egg hatch. This study demonstrates that several bioflavonoids stimulate oviposition by C. maculata and could be useful for mass rearing programs.